THE EFFECT OF NEOLOGISMS ON TRANSLATION - Shokirov Manuchekhr Shamsidinovich (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract: This study investigates the techniques utilized by simultaneous interpreters to manage neologisms during interpretation. It examines the difficulties interpreters encounter and proposes methods to enhance interpretation quality. Simultaneous interpretation demands real-time processing and translation of speech, posing distinct challenges. Speech compression has emerged as a technique to enhance accuracy and understanding. This paper explores the implementation of speech compression in simultaneous interpretation and its effects on interpreter performance.